Gremlin2 Activates Fibroblasts to Promote Pulmonary Fibrosis Through the Bone Morphogenic Protein Pathway - Huan, Caijuan; Xu, Wangting; Liu, Yaru; Ruan, Kexin; Shi, Yueli; Cheng, Hongqiang; Zhang, Xue; Ke, Yuehai; Zhou, Jianying (Frontiers in Molecular Biosciences, 2021)
Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease causing unremitting extracellular matrix deposition. Transforming growth factor-β (TGF-β) superfamily involves bone morphogenetic proteins (BMPs) and TGF-β, and the balance between the activation of TGF-β-dependent SMADs (Smad2/3) and BMP-dependent SMADs (Smad1/5/8) is essential for fibrosis process. GREM2, initially identified as a TGF-β-inducible gene, encodes a small secreted glycoprotein belonging to a group of matricellular proteins, Gremlin2, but its role in lung fibrosis is not clear. Here, we identified Gremlin2 as a key regulator of fibroblast activation. Gremlin2 was highly expressed in the serum and lung tissues in IPF patients. Bleomycin-induced lung fibrosis model exhibited high expression of Gremlin2 in the bronchoalveolar lavage fluid (BALF) and lung tissue. Isolation of primary cells from bleomycin-induced fibrosis lung showed a good correlation of Gremlin2 and Acta2 (α-SMA) expressions. Overexpression of Gremlin2 in human fetal lung fibroblast 1 (HFL-1) cells increased invasion and migration. Furthermore, Gremlin2 regulates fibrosis through mediating TGF-β/BMP signaling, in which Gremlin2 may activate TGF-β signaling and inhibit BMP signaling. Therefore, we provided in vivo and in vitro evidence to demonstrate that Gremlin2 may be a potential therapeutic target for the treatment of IPF.